2007
DOI: 10.1159/000107470
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Descending Colon: Report of a Case and Literature Review

Abstract: It is very rare that squamous cell carcinoma (SCC) arises from colorectal epithelium. An 89-year-old man was treated in 2001 with chief complaints of anorexia, abdominal pain, and low grade fever. The histological diagnosis as SCC was determined by biopsy during a colonoscopy. We diagnosed primary SCC of the colon because except in the colon no malignant lesions were found by systemic CT. Surgical complete resection was performed. However, he died three months after surgical resection because of hepatic metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The colorectal SCCs appear to be more frequently locally invasive and more likely to involve regional lymph nodes than the adenocarcinomas, probably due to delayed diagnosis [6]. In this case, the tumor was pT3 with lymph node involvement.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The colorectal SCCs appear to be more frequently locally invasive and more likely to involve regional lymph nodes than the adenocarcinomas, probably due to delayed diagnosis [6]. In this case, the tumor was pT3 with lymph node involvement.…”
Section: Discussionmentioning
confidence: 73%
“…It is very rare that SCC arises from the colorectal epithelium [6]. Schmidtman published the first report of a pure SCC of the colon in 1919 [6]. Since then, less than 150 cases have appeared in the literature [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic studies of colorectal adenocarcinomas have identified areas of squamous differentiation, suggesting the possibility that these carcinomas may arise from preexisting adenomas or adenocarcinomas. 4,5,8 Other coexisting conditions associated with SCC of the colorectum include colonic duplication 15 and the presence of malignancies, such as ovarian, prostate, endometrial, and breast cancer. 2,3 Patients with second malignancies may have a genetic predisposition for tumor formation, but information on this possibility is not available in patients with colorectal SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, Murakami et al described the first case of a pure SCC of the colon in 1974 [13]. It has been suggested that a number of criteria must be satisfied before a diagnosis of primary squamous cell carcinoma of the large bowel is entertained [3,14,15]: (1) there must be no evidence in any other organ of a squamous cell carcinoma that might spread directly into the lower bowel or provide a source of intestinal metastases, (2) the affected bowel should not be involved in a fistulous tract lined with squamous cells (colocutaneous fistulas have been described in association with squamous cell cancer), (3) when squamous cell carcinoma occurs in the rectum, care must be taken to exclude origin from the anal canal (that is, there should be a lack of continuity between the lesion and the anal canal epithelium), and (4) SCC must be confirmed by histological analysis. Our case satisfied all the above criteria.…”
Section: Discussionmentioning
confidence: 99%